Fabrication of Oriented n‐Type Thermoelectric Polymers by Polarity Switching in a DPP‐Based Donor–Acceptor Copolymer Doped with FeCl3. (27th March 2021) - Zeng, Huiyan; Mohammed, Mohammed; Untilova, Viktoriia; Boyron, Olivier; Berton, Nicolas; Limelette, Patrice; Schmaltz, Bruno; Brinkmann, Martin
Abstract: n‐Type‐doped polymers are key elements to fabricate all‐polymer thermoelectric generators but they are challenging to produce. Herein, a new strategy is proposed, which is based on polarity switching upon doping of a donor–acceptor (D–A) copolymer based on diketopyrrolopyrrol (DPP) and quintethiophene (5T) with FeCl3 . Polarity switching from p‐type to n‐type is observed upon increasing the doping concentration of FeCl3 . An analysis based on nonmonotonic density of states is proposed, which accounts for the main experimental trends and demonstrates that the polarity switch is governed by the electronic band filling that is determined by the dopant concentration. The influence of the curvature of the density of states is in addition discussed and a complete description of the doping induced transport regimes is proposed. This polarity switching depends on the molecular weight Mn of the polymer and shifts to higher FeCl3 concentrations with increasing Mn . This behavior is attributed to the change of the width of the density of states with Mn . The combination of polarity switching and alignment is a means to produce n‐type‐like oriented and conducting polymers with enhanced power factors up to 10 µW K −2 m −1 along the chain direction. Abstract : Combination of p→n polarity switching and polymer alignment of a low bandgap polymer produces n‐type‐like conducting polymers with enhanced thermoelectric power factors up to 10 µW K −2 m −1 . An analysis based on nonmonotonic density of states accounts for the main experimental trends and demonstrates that the polarity switch is governed by the electronic band filling, i.e., the dopant concentration.